RANCANG BANGUN ALAT PERBAIKAN FAKTOR DAYA UNTUK AC (AIR CONDITIONER) SECARA OTOMATIS - Darmawan, Alfian Fajar; Rahma Wati, Farah Aulia; Muhaimin, Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Analysis of the total capacity and the cost of the unused power in the electricity network is influenced by the electronic equipment used. It is inevitable that current electronic devices have experienced rapid growth and has become a primary need that can not be separated from public life. The problems faced by consumers PLN, especially in dynamic electronic equipment such as AC (Air Conditioner) that is used is poor quality power factor caused by the electrical load is inductive. Power quality is good if you have more than 0.85 power factor (cos Ï> 0.85) thus increasing the efficiency of electric power, voltage drop and power loss unfortunate-. To improve the power factor (cos Ï) of the power system with inductive loads required a reactive power compensator. This compensation can be done by adding a capacitor bank that serves as a compensator or memberbaiki Cos value. The results of a prototype of the tool box containing a capacitor bank that can compensate or correct the power factor value automatically.Keywords: air conditioner, reactive power, power factor, capacitor bank